Linnaea borealis L. в Україні - Прядко, О.І. (Український ботанічний журнал, 2011)
Дана характеристика распространения Linnaea borealis L. в Украине — одного из наиболее редких видов украинской флоры. Рассматриваются местонахождения L. borealis в Карпатах и на равнине. Местонахождения вида, выявленные раньше на равнине Украины, около 40 лет не подтверждаются. Приводится характеристика найденного автором местонахождения L. borealis на севере Западного Полесья, на территории НПП «Припять—Стоход». Distribution of Linnaea borealis, one of the most rare species in the Ukrainian flora listed in the Red Data Book of Ukraine, is described. For the last 40 years the species was not recorded in the previously known localities in the plain part of Ukraine. Data on a new locality of Linnaea borealis in the northern part of West Polissia, within the Prypiat— Stokhid National Nature Park, are provided.